1998
DOI: 10.1258/002367798780600007
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery distribution in Macaca fascicularis (Cynomolgus)

Abstract: SummaryThe studies were performed using stereomicroscopic dissection, and light microscopy examination on hearts of healthy and fertile non-human primates (Macaca fascicularis) of both sexes. The results indicate that the anatomy of the coronary arteries offers points of similarity as well as departure from humans. The blood supply to the hearts was by left [LCAI and right (RCA) coronary arteries. The LCA averaged 1.78 ± 0.29 (SDlmm (range 1.40-2.40 mm) in external diameter at its origin, and 4.34 ± 1.29 (SD)m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 8 publications
4
18
0
2
Order By: Relevance
“…This study has revealed a. coronaria sinistra to be larger than a. coronaria dextra in accordance with literature (Tecirlioglu et al., 1978; Dursun, 1979; Karadag and Soygüder, 1989; Teofilovki‐Parapid et al., 1993; Teofilovski‐Parapid and Kreclovic, 1998; Aksoy and Karadag, 2002; Dyce et al., 2002).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This study has revealed a. coronaria sinistra to be larger than a. coronaria dextra in accordance with literature (Tecirlioglu et al., 1978; Dursun, 1979; Karadag and Soygüder, 1989; Teofilovki‐Parapid et al., 1993; Teofilovski‐Parapid and Kreclovic, 1998; Aksoy and Karadag, 2002; Dyce et al., 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Although the five to six branches originating from ramus interventricularis paraconalis and extending to ventriculus dexter and ventriculus sinister were defined as a. adiposa by Karadag and Soygüder (1989), these arteries were determined to be a. septalis which supply septum interventriculare in accordance with literature (Tecirlioglu et al., 1978; Dursun, 1979; Bisaillon, 1981; Karadag and Soygüder, 1989; Taha and Abel‐Magied, 1996; Teofilovski‐Parapid and Kreclovic, 1998).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations